Orbital Reconstruction: Prefabricated Implants, Data Transfer, and Revision Surgery - Bittermann, Gido; Metzger, Marc Christian; Schlager, Stefan; Lagrèze, Wolf Alexander; Gross, Nikolai; Cornelius, Carl-Peter; Schmelzeisen, Rainer (Facial Plastic Surgery, 2014)
External impact to the orbit may cause a blowout or zygomatico-maxillary fractures. Diagnosis and treatment of orbital wall fractures are based on both physical examination and computed tomography scan of the orbit. Injuries of the orbit often require a reconstruction of its orbital walls. Using computer-assisted techniques, anatomically preformed orbital implants, and intraoperative imaging offers precise and predictable results of orbital reconstructions. Secondary reconstruction of the orbital cavity is challenging due to fractures healed in malposition, defects, scarring, and lack of anatomic landmarks, and should be avoided by precise primary reconstruction. The development of preformed orbital implants based on topographical analysis of the orbital cavity was a milestone for the improvement of primary orbital reconstruction.
Keywords: orbital reconstruction; computer-assisted surgery; preformed orbital implant; intraoperative imaging